Flavoured Additives in Ruminant Nutrition: A Review - Kalam, Sanket; Savsani, H. H.; Chavda, M. R.; Odedra, M. D.; Deendayal; Naliyapara, H. P.; Patel, S.D.; Belim, S.Y. (Indian Journal of Animal Nutrition, 2023)
The Indian livestock population is growing exponentially and with limited available fodder for livestock, it is becoming difficult to obtain optimum production from the animals. Constraints of fodder availability force to use of unconventional feedstuffs. Palatability of certain feedstuff depends on the pre-and post-ingestive feedback which comprises of smell, taste, texture and flavour of feed and aversion and preference towards particular feed caused due to those factors. Unconventional feeds have low palatability which impacts their intake and thus the production. Flavoured additives are substances that are added to those unconventional feedstuffs to improve their palatability by masking the unpleasant characteristics present in them and thus enhancing their intake and production of animals. The preference of animals toward particular feed changes with the taste, sweet and umami taste shows positive preference whereas bitter tastes show negative preference. Flavoured additives increase dry matter intake, average daily gain, and weight gain in growing animals whereas in dairy animals it improves dry matter intake, milk yield, milk fat percentage, feed efficiency and reduces loss of body condition and improves energy balance in the early lactating cow. There are a few challenges for manufacturing livestock ration and raw material quality and availability is the major cause that impact the cost of production and those challenges can be overcome by the use of flavoured additives to produce economic ration.